A survey of data recovery on flash memory - Van Dai Tran; Dong-Joo Park Park (Institute of Advanced Engineering and Science, 2020)
In recent years, flash memory has become more widely used due to its advantages, such as fast data access, low power consumption, and high mobility. However, flash memory also has drawbacks that need to be overcome, such as erase-before-write, and the limitations of block deletion. In order to address this issue, the FTL (Flash Translation Layer) has been proposed with useful functionalities like address mapping, garbage collection, and wear-leveling. During the process of using, the data may be lost on power failure in the storage systems. In some systems, the data is very important. Thus recovery of data in the event of the system crash or a sudden power outage is of prime importance. This problem has attracted attention from researchers and many studies have been done. In this paper, we investigate previous studies on data recovery for flash memory from FTL processing solutions to PLR (Power Loss Recovery) solutions that have been proposed by authors in the conference proceeding, patents, or professional journals. This will provide a discussion of the proposed solutions to the data recovery in flash memory as well as an overview.